2022
DOI: 10.1038/s41467-022-33228-6
|View full text |Cite
|
Sign up to set email alerts
|

The augmin complex architecture reveals structural insights into microtubule branching

Abstract: In mitosis, the augmin complex binds to spindle microtubules to recruit the γ-tubulin ring complex (γ-TuRC), the principal microtubule nucleator, for the formation of branched microtubules. Our understanding of augmin-mediated microtubule branching is hampered by the lack of structural information on the augmin complex. Here, we elucidate the molecular architecture and conformational plasticity of the augmin complex using an integrative structural biology approach. The elongated structure of the augmin complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…Based on our binding experiments with the two tetrameric subcomplexes, we suspect that this second binding site must be located somewhere within T-II, since importins do not bind T-III. However, we could not determine the location of this second importin-α binding region due to the lack of obvious predicted NLS sequences and because the entwined structure of the remaining T-II subunits prevents any other augmin fragments from folding correctly and thus retaining function (Gabel et al, 2022; Travis, 2022; Zupa, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our binding experiments with the two tetrameric subcomplexes, we suspect that this second binding site must be located somewhere within T-II, since importins do not bind T-III. However, we could not determine the location of this second importin-α binding region due to the lack of obvious predicted NLS sequences and because the entwined structure of the remaining T-II subunits prevents any other augmin fragments from folding correctly and thus retaining function (Gabel et al, 2022; Travis, 2022; Zupa, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Within T-II, there are two MT binding sites (Hsia et al, 2014; Travis et al, 2022a; Wu et al, 2008). The primary MT binding site was localized to the augmin subunit Haus8, within its intrinsically-disordered N-terminus (Hsia et al, 2014; Wu et al, 2008), while a second, minor MT binding site was very recently located within the Haus6 subunit (Travis et al, 2022a; Zupa et al, 2022). Thus, augmin promotes branching MT nucleation by recruiting γ-TuRC to the side of the MT (Alfaro-Aco et al, 2020; Song et al, 2018; Tariq et al, 2020; Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In their elegant work, Gabel et al, Zupa et al and Travis et al elucidate the molecular architecture and conformational plasticity of the augmin holocomplex from human 8 and X. laevis 9,10 . They integrated Artificial Intelligence-based structure prediction (ColabFold 11 or AlphaFold-Multimer 12 ) with complimentary structural biology techniques, such as single-particle cryogenic electron microscopy (cryo-EM) and cross-linking mass spectrometry, or more classic model validation using bulky tags visualised by negative stain EM.…”
Section: Determining the Structure Of The Augmin Complexmentioning
confidence: 99%
“…The eight subunits of the augmin complex have been reported to form two biochemically distinct subcomplexes, called tetramer T-II (containing HAUS2, 6, 7, and 8) and tetramer T-III (containing HAUS1, 3, 4, and 5) (Lawo et al 2009). Recent cryo-electron microscopy and single particle analysis studies showed that both tetramers together form an interconnected, highly flexible Y-shaped octameric complex (with a V-shaped head and a filamentous tail) (Gabel et al 2022, Zupa et al 2022, Travis et al 2022). The primary microtubule binding site has been localized to the intrinsically-disordered N-terminus of HAUS8 (Hsia et al 2014, Wu et al 2008), while a second, minor microtubule binding site was recently located within the HAUS6 subunit (Travis et al 2022, Zupa et al 2022), locating both binding sites to the V-shaped head.…”
Section: Introductionmentioning
confidence: 99%
“…Recent cryo-electron microscopy and single particle analysis studies showed that both tetramers together form an interconnected, highly flexible Y-shaped octameric complex (with a V-shaped head and a filamentous tail) (Gabel et al 2022, Zupa et al 2022, Travis et al 2022). The primary microtubule binding site has been localized to the intrinsically-disordered N-terminus of HAUS8 (Hsia et al 2014, Wu et al 2008), while a second, minor microtubule binding site was recently located within the HAUS6 subunit (Travis et al 2022, Zupa et al 2022), locating both binding sites to the V-shaped head. In vitro experiments suggest that several augmin complexes together recruit γTURC (Zhang et al 2022), but how the binding of augmin to microtubules is controlled remains unknown.…”
Section: Introductionmentioning
confidence: 99%